Nursing Care of Children : PN edition 7.1 ; review module - Wissman, Jeanne; Knippa, Audrey; Assessment Technologies Institute (s.l. : ATI, 2008)
"The overall goal of this Assessment Technologies Institute, LLC (ATI) Content Mastery Series module is to provide nursing students with an additional resource for the focused review of "Nursing Care of Children" content relevant to NCLEX-PN preparation and entry level nursing practice"--Preface.
Includes bibliographical references.
Keywords: Pediatric nursing -- Examinations, questions, etc; Nursing -- Examinations, questions, etc; National Council Licensure Examination for Practical/Vocational Nurses; Nurses -- Licenses -- United States -- Examinations -- Study guides